Caecal Microbiota of Experimentally Campylobacter jejuni-Infected Chickens at Different Ages - Hankel, Julia; Jung, Klaus; Kuder, Henrike; Keller, Birgit; Keller, Christoph; Galvez, Eric; Strowig, Till; Visscher, Christian (Frontiers in Microbiology, 2019)
Campylobacter jejuni is the most common bacterial cause of foodborne zoonosis in the European Union. Infections are often linked to the consumption and handling of poultry meat. The aim of the present study was to investigate the caecal microbiota of birds infected with C. jejuni at different ages. Therefore, a total of 180 birds of the laying hybrid Lohmann Brown-Classic were housed in 12 subgroups of 15 animals each in three identically performed repetitions. Three birds per subgroup were experimentally infected with C. jejuni at an age of about 21 days and about 78 days (4.46±0.35 log10 CFU/bird). Twenty-one days after experimental infection, microbiome studies were performed on 72 caecal samples of dissected birds (three primary infected and three further birds/subgroup). Amplification within the hypervariable region V 4 of the 16S rRNA gene was performed and sequenced with the Illumina MiSeq platform. Statistical analyses were performed using SAS® Enterprise Guide® (version 7.1) and R (version 3.5.2). Both factors, the experimental replication (p < 0.001) and the chickens’ age at infection (p < 0.001) contributed significantly to the differences in microbial composition of the caecal samples. The factor experimental replication explained 24 % of the sample’s variability, whereas the factor age at infection explained 14 % thereof. Twelve out of 32 families showed a significantly different count profile between the two age groups, whereby strongest differences were seen for seven families, among them the family Camylobacteraceae (adjusted p = 0.003). The strongest difference between age groups was seen for a bacterial species that is assigned to the genus Turicibacter which in turn belongs to the family Erysipelotrichaceae (adjusted p < 0.0001). Correlation analyses revealed a common relationship in both chicken ages at infection between the absolute abundance of Campylobacteraceae and Alcaligenaceae, which consists of the genus Parasutterella. In general, concentrations of particular volatile fatty acids demonstrated a negative correlation to absolute abundance of Campylobacterceae, whereby the strongest link was seen for n-butyrate (-0.51141; p <0.0001). Despite performing identical consecutive repetitions, the factor experimental replication contributed more to the differences of microbial composition in comparison to the factor age at infection.